Leverage points to foster human-nature relations for sustainability transformation - Riechers, Maraja (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Despite warnings from scientists and from society starting in the 1970s, we have long overshot our planetary boundaries – eroding biodiversity, changing our landscapes, and polluting our soil and atmosphere. Yes, efforts to change the unsustainable trajectories of our Earth system have increased through, for example, the Millennium Goals, the Sustainable Development Goals, or the Aichi Targets, but to no avail. The interventions to increase sustainability are conflicting on local, national and global levels, and often prioritise quick-fixes and short-term solutions instead of tackling the root causes of the “sustainability gap”. We, hence, need to find “places to intervene in complex systems that bring about transformative change” (Meadows 1999) – a premise and concept that Donella Meadows calls “leverage points”. Based on her seminal work, a team from the Leuphana University has identified three “realms of leverage” in which changes may lead to system transformation (Abson et al. 2017). One of these realms is the reconnection of humans to nature. In this habilitation, I focus on this realm of leverage and aim to (1) enhance the understanding of the influence of landscape change on human-nature relations through empirical, place-based research and comparisons across landscapes in different countries and continents; (2) identify and clarify the new concepts of relational values and leverage points; and (3) highlight empirical evidence on leverage points to foster human-nature relations for sustainability transformation, building mainly on empirical work done in six landscapes in Transylvania, Romania and Lower Saxony, Germany, but also including case studies from Ethiopia and India, systematic literature reviews and conceptual pieces. This thesis showed that cultural landscapes are changing with astonishingly comparable trajectories toward unsustainable futures. Our earth’s current environmental and climate crisis will continue to erode the fundaments of sustainability, hence, re-connecting humans to nature is of outstanding significance for transformative change. Identifying leverage points and implementing an intervention to strengthen human–nature relations will be a great challenge in the coming years. One possible leverage point can be strengthening experiential and emotional dimensions, as they specifically shape the connections people have with cultural landscapes. Further, this thesis highlighted the importance of the interlinkages between shallow and deep leverage points. Our results show that structurally complex landscapes and structurally rich social relations mediated by nature are interlinked and strengthening one, may strengthen the other. Moreover, strengthening sense of place and a sense of agency may enable self- and re-organization of cultural landscapes by opening the possibility to renegotiate people’s values for values and the goals of the social-ecological system, which, in turn, may enhance the structural diversity of landscapes and small-scale agriculture. Our results presented in this thesis also lay the ground for the hypothesis that degrading landscapes might also degrade social relations, which, in turn, can lead to contrasts and conflicts between actors and social groups. Although much work is still necessary to foster transformative change, this thesis offers innovative approaches. This thesis created and popularised the “Leverage points perspective”, including “chains of leverage”, as well as producing novel insights on human-nature relations – such as the distinction of human-nature connectedness and relational values, classifying relational value groups and empirically assessing dimensions of human-nature connectedness and relational values concerning landscape change and landscape features. These novel contributions can have wide-ranging impacts on the scientific discussions and societal implementation of interventions for sustainability. Leverage points to foster human-nature relations for sustainability transformation

Trotz Warnungen von Wissenschaftler*innen und der Gesellschaft seit den 1970er Jahren haben wir unsere planetarischen Grenzen längst überschritten, mit der Konsequenz von sinkender Biodiversität, rapiden Landschaftsveränderungen und steigenden Treibhausgasemissionen. Die Bemühungen, diese nicht-nachhaltige Laufbahn unseres Erdsystems zu ändern, haben zwar zugenommen, z. B. durch die Millenniumsziele, die Ziele für nachhaltige Entwicklung oder das Übereinkommen über die biologische Vielfalt, aber ohne jeden Erfolg. Die Maßnahmen zur Verbesserung der Nachhaltigkeit sind auf lokaler, nationaler und globaler Ebene widersprüchlich und geben oft schnellen und kurzfristigen Lösungen den Vorrang. Wir müssen daher "Orte [finden], an denen in komplexe Systeme eingegriffen wird, um einen transformativen Wandel herbeizuführen" (Meadows 1999) – eine Prämisse und ein Konzept, das Donella Meadows „Leverage Points“ (Interventionspunkte) nennt. Basierend auf ihrer bahnbrechenden Arbeit hat ein Team der Leuphana Universität drei Bereiche identifiziert, in denen Veränderungen zu einer Systemtransformation führen können (Abson et al. 2017). Einer dieser Bereiche ist die Rückverbindung zwischen Mensch und Natur. In dieser Habilitation konzentriere ich mich darauf Interventionspunkte zu identifizieren, um Menschen wieder stärker mit der Natur zu verbinden. Diese Habilitation zielt darauf ab, (1) das Verständnis des Einflusses des Landschaftswandels auf die Mensch-Natur-Beziehungen durch empirische, ortsbezogene Forschung und Vergleiche zwischen Landschaften in verschiedenen Ländern und Kontinenten zu verbessern; (2) die neuen Konzepte der relationalen Werte und der „Leverage Points“ zu identifizieren und zu klären; und (3) empirische Belege für Interventionspunkte zur Förderung der Mensch-Natur-Beziehungen für die Nachhaltigkeitstransformation hervorzuheben. Diese Analysen basieren hauptsächlich auf empirischen Studien in sechs Studienstandorten/Landschaften in Siebenbürgen, Rumänien und Niedersachsen, Deutschland. Meine Arbeit hat gezeigt, dass sich die Kulturlandschaften in Europa und überall auf der Welt verändern, mit erstaunlich vergleichbaren Entwicklungen in Richtung einer nicht nachhaltigen Zukunft. Daher ist es für einen transformativen Wandel von herausragender Bedeutung, die Abwärtsspirale der zunehmenden Entkopplung von der Natur zu durchbrechen. Die Identifizierung von Interventionspunkten zur Stärkung der Mensch-Natur-Beziehungen wird in den kommenden Jahren eine große Herausforderung darstellen. Ein Interventionspunkt ist die Stärkung der Erlebnis- und Gefühlsdimensionen, die die Beziehungen der Menschen zur Kulturlandschaft besonders prägen. Darüber hinaus zeigen unsere Ergebnisse, dass strukturell komplexe Landschaften und strukturell reichhaltige, durch die Natur vermittelte soziale Beziehungen miteinander verknüpft sind und die Stärkung des einen auch das andere stärken kann. Darüber hinaus kann die Stärkung des Ortssinns und des Handlungssinns eine Selbst- und Reorganisation von Kulturlandschaften ermöglichen, indem sie die Möglichkeit eröffnet, die Werte der Menschen für die Werte und Ziele des sozial-ökologischen Systems neu zu verhandeln. Die in dieser Arbeit vorgestellten Ergebnisse legen den Grundstein für die Hypothese, dass die Degradierung von Landschaften auch zu einer Degradierung der sozialen Beziehungen, was wiederum zu Gegensätzen und Konflikten zwischen sozialen Gruppen führen kann. Die innovativen Ansätze dieser Habilitation beinhalten die „Leverage Points Perspektive“, „Chains of Leverage“, und einen Weg zur Standardisierung der Identifizierung von Leverage Points. Zusätzliche innovative Erkenntnisse über Mensch-Natur-Beziehungen betreffen die Unterscheidung von Mensch-Natur-Verbundenheit und relationalen Werten, die Klassifizierung von relationalen Werten und deren empirische Bewertung in Bezug auf Landschaftswandel und -merkmale.
Interventionspunkte zur Stärkung von Mensch-Naturbeziehungen für eine Nachhaltigkeitstransformation